中国农民健康保险需求影响因素的灰色关联分析 - 彭晓博; 孙祁祥 (保险研究, 2012)
随着老年人口增多,农村医疗支出也会增加.未来若单靠政府投入势必会带来沉重的财政支出负担,长期将难以持续.基于这一背景,作者认为应当大力发展商业健康保险,培育市场,尽快建立起多支柱的医疗保障体系.本文从需求角度出发,认为影响农民健康保险需求的因素主要包括经济、卫生资源和社会文化等因素,并采用三因素中的代表性变量进行灰色关联分析,结果显示,卫生资源和支付能力与健康保险需求具有较强的灰色关联度.Rural?residents'?medical?expenditure?will?increase?notably?as?the?surge?in?the?elderly?population.?There-?fore?it?will?lead?to?a?heavy?burden?on?government's?budget?if?the?increase?in?healthcare?expenditure?was?solely?born?by?the?government.?The?authors?suggested,?as?a?consequence,?the?importance?of?developing?a?multi-pillar?health?insurance?system?,which?should?include?government?subsidized?health?insurance?as?well?as?commercial?health?insurance,?should?be?recognized.?The?authors?analyzed?three?factors?which?were?hypothesized?to?be?correlated?with?farmers'?healthcare?demands?,which?included?economic?factors?,healthcare?resource?factors?as?well?as?social?and?cultural?factors.?Using?a?number?of?variables?measuringthe?above?three?factors,?the?authors?conducted?a?Grey?Relation?Analysis.?The?results?showed?that?farmers'?health?insurance?demand?was?significantly?correlated?with?economic?factors?,?as?well?as?healthcare?resource?factor.
Keywords: 健康保险需求; 影响因素; 灰色关联分析; health insurance demand; healthcare; grey relation analysis